New York City’s Harbor Siphons Water Tunnel - Michael S. Schultz; Colin Lawrence (Society for Mining, Metallurgy & Exploration, 2007)
Due to the planned deepening of the NY Harbor, NYCEDC/NYCDEP is planning to replace two existing water lines between Brooklyn and Staten Island with one deeper water pipe. The crossing, just north of the Verrazanno Bridge is 1.75 miles long. The new pipeline will be tunneled using gasketed concreted segmented liners. Apressurized face machine will be used through the soft ground. This will be the first subaqueous application using this technology in New York City. This paper discusses the planning, design and risk issues associated with the crossing and the challenging soil conditions that resulted in the decision to use a pressurized face machine.